Development and pilot study of an oral health literacy tool for older adults. Issue 4 (17th October 2019) - Wanichsaithong, Pinpinut; Goodwin, Michaela; Pretty, Iain A.
Abstract: Aim: Oral health literacy is emerging as an important element in oral health promotion, but few studies have been conducted in older adults. This work aimed to develop and validate the Test of Functional Health Literacy in Dentistry for Older Adults (OA‐TOFHLiD). Methods: The tool was developed by a researcher and then evaluated by experts for face validity. A convenience sample was conducted to recruit 105 older adults, aged more than 60 years in Chiang Mai, Thailand, in 2016. 2 existing health literacy tools and the newly developed test were administered and oral health statuses were examined by a dentist. Results: The mean age of the participants was 67.4 years (SD = 5.86). The OA‐TOFHLiD scores were positively correlated with education, income, self‐reported general literacy, health literacy scores and dental caries. However, it was negatively correlated with the number of decayed and missing teeth ( P  < .05). Cronbach's alpha was 0.88 and the intraclass correlation coefficient was 0.86. Conclusion: This study demonstrated that OA‐TOFHLiD has acceptable validity and reliability; however, it is suggested that the predictive validity of this tool should be improved.